Control strategy for optimising the thrust of a high‐speed six‐phase linear induction motor. Issue 11 (10th June 2020) - Han, Yi; Nie, Ziling; Xu, Jin; Zhu, Junjie; Sun, Jun
Abstract : In this study, a short primary six‐phase linear induction motor (LIM) operating in high‐speed non‐periodic transient conditions is used as an object of study. In consideration of the coupling terms related to the dynamic end effect, the motor model is simplified and the vector control equation is deduced. A vector control strategy for the real‐time modification of slip‐frequency and torque current is proposed for dynamic thrust compensation. On this basis, considering the problems of thrust decay caused by dynamic end effect and dc‐link voltage drop, this study puts forward a field‐weakening control method to keep thrust constant before its decrease in the field‐weakening region. The method makes it possible for the LIM to overcome the thrust decay and the narrowing of voltage limits under the high‐speed operating conditions. The simulation and experimental results show that the proposed control strategies are useful for optimising the thrust in the transient process thus to realise the high‐speed operation of the motor.